(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on the discussion of the biochemical mechanisms of origin and development of endemic icterohemoglobinuria in karakul sheep grazing in the natural pastures of the Red Sand biogeochemical oasis on the basis of scientific sources and research results.